Analysis of the Assurance Quality of BPJS Healthcare Services at Health Center - Alfina Damayanti; Hendra Sukmana (Indonesian Journal of Public Policy Review, 2023)
The Purpose of this study was to determine, describe, and the analyze the quality of BPJS Healthcare Services at the Sukodono Health Center Sidoarjo. Qualitative descriptive research method through interviews, observation, and documentation. Determination of informants was carried out using a purposive sampling method wich involved the Head of PIC BPJS, Responsible for BPJS service network, BPJS Services Administration Employees, and Patients who used BPJS Services. Data analysis techniques using Miles Hubberman through data collection, data reduction, data presentation, drawing conclusions. The results of this study indicate that BPJS Healthcare Services at the Sukodono Health Center Sidoarjo are assessed from dimensions Assurance (guarantee) courtesy and cost guarantee are good enough and in accordance with BPJS Healthcare rules. However, inhibiting factors include the performance target of the puskesmas being too high, the lack of public awaraness, and regular employee training.